Prediction of construction and assembly production in the province of Lower Silesia. Part I - Rogalska, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article is the first part of the series „Prediction construction and assembly production in Lower Silesia.” It was assumed that salary of employees will be one of the independent variables to determine the volume of production. Salaries of employees was predicted, using multiple regression and autoregressive moving average SARIMA methods. An analysis of the results was carried out. The errors ME, MAE, MPE, MAPE and Theil coefficients I, I2, I12, I22, I32 were calculated. Multiple regression equation with 12 predictors was set. Predictors were selected from among the 53 independent variables. Forecasted data were obtained for construction and assembly production prediction.